High Intensity Long Interval Sets Provides Similar Enjoyment as Continuous Moderate Intensity Exercise. The Tromsø Exercise Enjoyment Study - Sagelv, Edvard H.; Hammer, Tord; Hamsund, Tommy; Rognmo, Kamilla; Pettersen, Svein Arne; Pedersen, Sigurd (Frontiers in Psychology, 2019)
Objective High intensity interval exercise sessions with interval sets over 3 min may provide superior cardiorespiratory fitness benefits. To our knowledge, the exercise enjoyment of interval sets over 3 min is not yet elucidated. The aim of this study was to examine exercise enjoyment following one session with four intervals of 4 min high intensity exercise (HIIE) versus one session of 45 min moderate intensity continuous exercise (CE) in iso-caloric conditions using a randomized crossover design. Methods Seven young healthy participants were recruited to undergo two different exercise sessions in a randomized order: (1) 4 × 4 min intervals at >90% of maximum heart rate (HRmax) with 3 min of rest between interval sets, and (2) 45 min CE at 70% of HRmax. Peak oxygen uptake and HRmax were evaluated prior to the experiment. The participants reported their perceived exercise enjoyment using the 18-item physical activity enjoyment scale (PACES) questionnaire and their rating of perceived exertion (RPE) using Borg’s 6–20 scale. Results There was no difference in the PACES score between the high intensity interval exercise session [median: 95.5 (inter-quartile range: 21.8)] and the moderate intensity CE session [91.0 (13.5), p = 0.36, r = −0.22]. The participants reported a higher RPE in the high intensity interval exercise session [16.5 (2.0)] compared with the CE session [9.0 (2.0), p = 0.01, r = −0.88]. Conclusion Similar exercise enjoyment was reported following four high intensity intervals of 4 min compared with a moderate intensity CE session in this randomized crossover study with iso-caloric conditions. If enjoyment is a mediating factor for engaging in exercise, one should expect a similar probability of exercise adherence following high intensity 4 min intervals and continuous moderate intensity exercise when prescribing aerobic exercise as preventive medicine.